Fouling assemblages of native, non-indigenous and cryptogenic species on artificial structures, depths and temporal variation - Albano, Mariano Javier (2019)
Non-indigenous species (NIS) are prominent constituents of fouling communities. NIS can cause biodiversity loss and change community structure through the local elimination of native species. Ports are the main focus of NIS and artificial structures are becoming spots of introduction. Community composition can vary with depth and time. In this context, this work aimed to assess substrate (concrete and wood), vertical position (near-surface and near-bottom) and month variations on the abundance of fouling invertebrates' assemblages represented by native, NIS and cryptogenic species within the Mar del Plata port, Argentina. Monthly subtidal samples were taken scraping from fouling assemblages on substrates and vertical position in the port. Assemblages on substrate, depth and time showed similar species composition patterns. Native, NIS and cryptogenic species vary in mean abundances on each substrate, depth and month. Diversity indices on concrete and on near-bottom revealed higher values. High species specific response of NIS (compared to native), found in this study along the temporal fluctuations in fouling communities was registered. A long term monitoring and future studies might consider including more substrates type and an intermediate depth, since they will provide better knowledge about the fouling invasions.